FG-3019 anti-connective tissue growth factor monoclonal antibody: results of an open-label clinical trial in idiopathic pulmonary fibrosis. Issue 5 (10th March 2016) - Raghu, Ganesh; Scholand, Mary Beth; de Andrade, João; Lancaster, Lisa; Mageto, Yolanda; Goldin, Jonathan; Brown, Kevin K.; Flaherty, Kevin R.; Wencel, Mark; Wanger, Jack; Neff, Thomas; Valone, Frank; et al.
FG-3019 is a fully human monoclonal antibody that interferes with the action of connective tissue growth factor, a central mediator in the pathogenesis of fibrosis. This open-label phase 2 trial evaluated the safety and efficacy of two doses of FG-3019 administered by intravenous infusion every 3 weeks for 45 weeks in patients with idiopathic pulmonary fibrosis (IPF). Subjects had a diagnosis of IPF within the prior 5 years defined by either usual interstitial pneumonia (UIP) pattern on a recent high-resolution computed tomography (HRCT) scan, or a possible UIP pattern on HRCT scan and a recent surgical lung biopsy showing UIP pattern. Pulmonary function tests were performed every 12 weeks, and changes in the extent of pulmonary fibrosis were measured by quantitative HRCT scans performed at baseline and every 24 weeks. FG-3019 was safe and well-tolerated in IPF patients participating in the study. Changes in fibrosis were correlated with changes in pulmonary function. Further investigation of FG-3019 in IPF with a placebo-controlled clinical trial is warranted and is underway. FG-3019 demonstrated good outcomes in changes in pulmonary function and extent of pulmonary fibrosis in IPF http://ow.ly/Xn7B4